Regional Government Policy in Preventing Illegal Drug Trade Case Study: North Sumatera - Prasetya, Muhammad Novan (Journal of Islamic World and Politics, 2018)
abstractIndonesia with abundant natural resources and the location is in a strategic area in international trade is become an important factor to look at the increasing problem of drug trafficking. The important issue in Indonesia is the policy in the State of Indonesia is considered still lacking in terms of handling drugs. This research is a descriptive analytic research with qualitative methods. The author provides an overview and explain the efforts government in North Sumatra in tackling the trafficking and distribution of illegal narcotics are even already global.In ASEAN, Indonesia is the largest market for drug sales, while the country is the largest importer of China and Thailand. For Indonesia, geopolitics is the policy in order to achieve national goals by utilizing the advantages geographical position of the country is based on scientific knowledge about the geographical conditions. The network of drug syndicates from China who control distribution business in Indonesia.            In the area of North Sumatra, one of the sea track with high drug access is in Medan Belawan. BelawanPort, Medan is one of a number of ports that be the main concern of the apparatus because of prone to drug smuggling. In the region of North Sumaterawith the crusialstatus of acute drug, indicating that the handling of the border region of the ocean is still less to see the data obtained from the North Sumatra Police that the number of suspected cases of drug abuse in 2015 reached 6,267 people, and then increased in 2016 became 6,534 people. Belawan Pelawan Police Station itself occupies the second position with the number of 384 cases with 452 suspects. High incidence of drug abuse in North Sumatra is because North Sumatra region is the entrance and transit of drugs from outside to Indonesia.From the case study above, it can be taken a center line of the vulnerability of the various policies related to drug abuse, then it is not possible the increase of drugs in the region of North Sumatra, Medan can be overcome.